Hi‐Res scan mode in clinical MDCT systems: Experimental assessment of spatial resolution performance. Issue 5 (19th April 2016) - Cruz‐Bastida, Juan P.; Gomez‐Cardona, Daniel; Li, Ke; Sun, Heyi; Hsieh, Jiang; Szczykutowicz, Timothy P.; Chen, Guang‐Hong
Abstract : Purpose: The introduction of a High‐Resolution (Hi‐Res) scan mode and another associated option that combines Hi‐Res mode with the so‐called High Definition (HD) reconstruction kernels (referred to as a Hi‐Res/HD mode in this paper) in some multi‐detector CT (MDCT) systems offers new opportunities to increase spatial resolution for some clinical applications that demand high spatial resolution. The purpose of this work was to quantify the in‐plane spatial resolution along both the radial direction and tangential direction for the Hi‐Res and Hi‐Res/HD scan modes at different off‐center positions. Methods: A technique was introduced and validated to address the signal saturation problem encountered in the attempt to quantify spatial resolution for the Hi‐Res and Hi‐Res/HD scan modes. Using the proposed method, the modulation transfer functions (MTFs) of a 64‐slice MDCT system (Discovery CT750 HD, GE Healthcare) equipped with both Hi‐Res and Hi‐Res/HD modes were measured using a metal bead at nine different off‐centered positions (0–16 cm with a step size of 2 cm); at each position, both conventional scans and Hi‐Res scans were performed. For each type of scan and position, 80 repeated acquisitions were performed to reduce noise induced uncertainties in the MTF measurements. A total of 15 reconstruction kernels, including eight conventional kernels and seven HD kernels, were used to reconstruct CT images of the bead. An ex vivo animal study consisting of a bone fracture model was performed to corroborate the MTF results, as the detection of this high‐contrast and high frequency task is predominantly determined by spatial resolution. Images of this animal model generated by different scan modes and reconstruction kernels were qualitatively compared with the MTF results. Results: At the centered position, the use of Hi‐Res mode resulted in a slight improvement in the MTF; each HD kernel generated higher spatial resolution than its counterpart conventional kernel. However, the MTF along the tangential direction of the scan field of view (SFOV) was significantly degraded at off‐centered positions, yet the combined Hi‐Res/HD mode reduced this azimuthal MTF degradation. Images of the animal bone fracture model confirmed the improved spatial resolution at the off‐centered positions through the use of the Hi‐Res mode and HD kernels. Conclusions: The Hi‐Res/HD scan improve spatial resolution of MDCT systems at both centered and off‐centered positions.